Use of Artificial Intelligence in HR Recruitment and Selection in Start-up Companies - Rovanita Rama; Jasmin Jasmin; Arief Yanto Rukmana; Said Hamzali; Arnes Yuli Vandika (West Science Social and Humanities Studies, 2024)
This bibliometric study analyzes the evolving landscape of human resource management (HRM), emphasizing the integration of technology into HR practices, particularly in recruitment and selection processes. Utilizing VOSviewer, the research maps the co-occurrence of keywords within a comprehensive dataset, revealing dominant themes, trends over time, and less explored areas. The analysis identifies core thematic clusters such as "human resource management," "recruitment," and "analytics," highlighting the significant focus on optimizing traditional HR functions through technological advancements. The study observes a marked shift in research trends, particularly influenced by the challenges posed by the COVID-19 pandemic, which accelerated the adoption of remote work technologies and digital HR tools. The visualization also identifies underexplored research opportunities in areas like "blockchain" and "internet," suggesting potential for groundbreaking research in enhancing HR operations. Furthermore, the network analysis underscores the importance of author collaboration in expanding the multidisciplinary scope of HRM research. This study contributes to the understanding of HRM's dynamic evolution and outlines strategic directions for future research, ensuring HR practices align with technological advancements and organizational needs.